Effects of hydraulic retention time and influent alkalinity on the performance of bio-electrochemical system assisted anaerobic baffled reactor. Issue 53 (13th November 2016) - JingRui, Zhang; Gefu, Zhu; Xiaofang, Pan; Ajay Kumar, Jha; Lin, Liu; Xu, Huang; Chaoxiang, Liu
Abstract: The effect of hydraulic retention time (HRT) and influent alkalinity on the performance of bio-electrochemical system assisted anaerobic baffled reactor (BES-ABR) was investigated in this study. The results indicated that as the HRT and influent alkalinity increase, COD removal efficiencies were enhanced correspondingly. The maximum COD removal efficiency of 97.4% was obtained at HRT of 48 h and COD of 4, 000 mg/L. The maximum COD removal efficiency of 87.5% was obtained at influent alkalinity of 1, 300 mg CaCO3 /L and COD of 5, 000 mg/L. Analysis of microbial community suggested that electrogenic micro-organisms were responsible for the better performance and stability of the system. The establishment and performance of this novel and efficient partial two-phase separation of BES-ABR strongly depended on the regulation of HRT and influent alkalinity.